Professionals' ideas and observations on preschoolers' experiences with physical symptoms: a qualitative interview study - Sterre van der Ziel; Janna M. Gol; Daniël Schoemaker; Judith G. M. Rosmalen; Michel J. van Vliet (BMC, 2024)
Abstract Background Preschoolers experience physical symptoms, like abdominal pain or minor injuries, almost every day. These experiences may shape how they deal with health issues later in life. To gain insight into these early life experiences, information from multiple perspectives is useful. This qualitative study aimed to explore important themes in preschoolers' experience of physical symptoms, using adult professionals from various backgrounds as informants. Methods 20 semi-structured interviews were performed with professionals from different fields in healthcare and education, to learn about their ideas and observations on preschoolers' experiences with physical symptoms. The interviews were verbatim transcribed and coded in Atlas.ti by two independent coders, after which thematic content analysis was applied to define themes. Results Three themes emerged from the interviews: unawareness, seeking attention, and parental influence. Unawareness refers to the professionals' idea that preschoolers have limited cognitions about causes and consequences of physical symptoms. Seeking attention was described as important for preschoolers with symptoms, both as comfort and in a social context. Professionals described diminished attention-seeking behavior in preschoolers with more severe symptoms. Parental influence was seen as highly relevant in preschoolers' experiences with physical symptoms, with both supportive and disruptive aspects. Healthcare professionals differed from educational professionals in their observations and ideas, especially about underlying mechanisms influencing symptoms. Conclusions Professionals report attention-seeking and parental influence as important factors in preschoolers with physical symptoms, and they report limited cognitions about causality. Professionals in healthcare and education show different perceptions, suggesting the importance of incorporating both views into research.